Resource-Based View (RBV) Analysis of Amil as Strategic Resource for Digital Zakat Management (Case Study at BAZNAS in Palu City) - Aisyah Alkaf; Ahmad Arief; Desy Kristiane (Al-Amwal : Journal of Islamic Economic Law, 2026)
Purpose  – This study investigates the practices and obstacles of digital zakat management at BAZNAS in Palu City, emphasizing effectiveness and efficiency in alignment with Article 3 (a) of Law Number 23 of 2011 about Zakat Management. Significant issues include insufficient digital literacy among the populace and a scarcity of human resources, notwithstanding the presence of technology. This study aims to delineate digital zakat practices and evaluate the competencies of amil as strategic assets through the Resource-Based View (RBV) viewpoint, employing the VRIO framework to actualize zakat digitization in alignment with sharia objectives and promote sustained excellence. Method  –  This qualitative research with a case study design involved 4 key informants namely the Head, Deputy Head III, Treasurer and IT staff of BAZNAS Palu City. Data was collected from semi-structured interviews, observations and documents analyzed based on the VRIO model. Result  – Despite an official website and the BAZNAS Management Information System (SIMBA), low community digital literacy and poor technology innovation due to a focus on current methods have limited BAZNAS Palu City's digital zakat impact. VRIO shows that Amil has some beneficial organizational traits, but few are substantial. Zakat digitization is challenging for muzkki and mustahik due to scarcity and immutability. Effective zakat administration requires strategic changes. According to the study, BAZNAS and other zakat agencies must improve amil's digital expertise and human resources to legally reform zakat. Implication  –  In practical terms, the result emphasizes the importance of BAZNAS and other zakat institutions strengthening the capabilities and contribute of amil by improving digital literacy and developing human resources so that the digital transformation of zakat can take place sustainably in accordance with applicable laws.